Pengaruh Stres Kerja terhadap Kinerja Karyawan Departemen Teknik PT. Pelindo Marine Service Surabaya melalui Burnout Sebagai Variabel Intervening - FATMA PRIYANTIKA, DEVI (Jurnal Ilmu Manajemen (JIM), 2018)
For companies pay attention to employee stress levels and burnout (employee fatigue) is something that needs to be done. Due to work stress and high employee fatigue will result in the performance of employees will be worse or decreased. The purpose of this study is to examine the effect of job stress on the performance of employees of the engineering department of PT. Pelindo Marine Service Surabaya through Burnout as intervening variable. This research is a type of research with quantitative approach, with the number of research samples as much as 42 employees of engineering department of PT. Pelindo Marine Service Surabaya, using Likert scale as measurement scale. Data analysis in this study using Partial Least Square (PLS) analysis techniques and with the help of SmartPLS 3.0 program. The result of this research indicates that there is a negative effect between work stress on employee performance, the negative effect between burnout on employee performance, the positive influence between work stress on burnout and work stress influence to employee performance through burnout as intervening variable.